1967
DOI: 10.1073/pnas.57.3.607
|View full text |Cite
|
Sign up to set email alerts
|

MACRONUCLEAR DNA SYNTHESIS IN Stentor : REGULATION BY A CYTOPLASMIC INITIATOR

Abstract: The large ciliate Stentor coeruleus lends itself well to microsurgical procedures. By combining these techniques with autoradiography after exposure of cells to thymidine-H3, it is possible to study mechanisms regulating the occurrence of macronuclear DNA synthesis during the cell growth cycle. Transfer of nuclei between cells which are synthesizing DNA and cells which are not can indicate whether DNA synthesis is determined by the continuous presence or absence of a cytoplasmic factor. Similar experiments inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…Scaling of ploidy with cell size agrees with observations that macronuclear DNA synthesis occurs throughout interphase in Stentor [38], and suggests DNA content may determine cell size in Stentor or vice versa.…”
Section: Resultssupporting
confidence: 82%
“…Scaling of ploidy with cell size agrees with observations that macronuclear DNA synthesis occurs throughout interphase in Stentor [38], and suggests DNA content may determine cell size in Stentor or vice versa.…”
Section: Resultssupporting
confidence: 82%
“…Kolodny and Gross (9) also reported differences in patterns of proteins synthesized during G2 phase and patterns obtained in other phases of the cell cycle. Numerous studies suggest that factors required for initiation of DNA synthesis are made in the cytoplasm (3,6,7,17,18, and others). Our results showed that the peak I protein was synthesized in the cytoplasm of cells traversing G1 and that synthesis declined as the cells entered S phase.…”
Section: Discussionmentioning
confidence: 99%
“…By culturing dividing organisms (stages 3-8) in a 3H-TdR containing medium for 30 min and then making autoradiographs of the organisms, DE TERRA (1967) found that label was always present above the nuclear nodes at stages 3 and 4, seldom present above coalescing nuclei (stage 5) and never present above the compacted, elongating and nodulating nuclei (stages 6-8). DNA synthesis thus occurs during the first four hours of the 8 hour division period (D) and stops at or near the time nuclear coalescence begins.…”
Section: D) Endoploid Cellsmentioning
confidence: 99%